DETERMINAN PENGELUARAN PANGAN 34 PROVINSI DI INDONESIA PADA MASA PANDEMI COVID-19 MENGGUNAKAN REGRESI KUANTIL - Yohanes, Rio; Asih Murwiati (Goodwood Publishing, 2025)
This study investigates the primary factors influencing household food expenditure in Indonesia, particularly in the context of the economic impacts of the Covid-19 pandemic, rising food insecurity (Prevalence of Undernourishment/PoU), and persistent income inequality (Gini Index). The research aims to analyze the influence of Provincial Minimum Wage (UMP), Gini Index, Food Insecurity Prevalence (PKP), and Non-Food Expenditure (PNM) on household food expenditure. Employing a quantitative approach with Quantile Regression, the study examines these relationships across various distribution points. The findings reveal that UMP negatively and significantly affects food expenditure at the 25th and 50th percentiles, while the Gini Index shows a positive and significant influence at the same quantiles. Furthermore, PKP negatively and significantly impacts food expenditure at the 75th and 85th percentiles. Conversely, PNM consistently exhibits a positive and significant relationship with food expenditure across all analyzed quantiles (25th, 50th, 75th, and 85th). These results offer valuable insights for policymakers in developing targeted strategies to enhance food security and promote economic well-being in Indonesia.